Environment Parameter Of Successful Edible Bird Nest Swiftlet House In Terengganu - Puspa Liza, Ghazali; Munirah, Abd Rahman; Chong, Ju Lian (2018)
Most edible bird nest (EBN) swiftlet farming industry enterpreneurs suffered losses due to lack of knowledge in providing the right environmental parameter factors in their EBN swiftlet houses as EBN production is influenced by various environmental parameter factors such as air temperature, surface temperature, relative humidity, light intensity, internal and external sound levels in swiftlet houses. This study compared environmental parameter factors in coastal, rural and urban areas in Terengganu to investigate environmental parameter factors that play a critical role in determining the success of a swiftlet ranching venture. Air and surface temperature, relative humidity, light intensity, and sound level were recorded in 30 EBN swiftlet houses in three different area; 10 in coastal, rural and urban area in Terengganu respectively. Mean EBN and individual swiftlet population were 81 nests, 210 individuals in rural; 53 nests, 137 individuals in coastal and 23 nests, 59 individuals in urban area. Rural area houses had most suitable range for swiftlet adaptation. EBN production was significantly higher in swiftlet houses with suitable environmental factors such as air and surface temperature were 30.1oC, relative humidity 83.7%, light intensity 0.16 lux, with sound 47dB (internal) and 68dB (external). As such, rural areas will be most productive to build EBN swiftlet house.